An evaluation of the role played by save the children in reducing child mortality in ward 13 Zhombe area, Zibagwe district . - Zirobwa, Fadzayi B. (Midlands State University, 2017)
The purpose of the research was to evaluate the role played by Save the Children Organisation in reducing child mortality in Ward 13 Zibagwe District. In conducting the study, both the interviews and focus group discussions were employed as the main research instruments. It is evident that most of the rural communities in Zimbabwe, Zibagwe District in particular have been facing child deaths due to various barriers such as poverty, socio-economic challenges and home deliveries to mention a few in their day to day lives. Therefore Save the Children Organisation through their programme of strengthening community participation in health was initiated as a way of trying to reduce the continuous deaths of pregnant women and children under the age of five due to health challenges faced in the community. However, in trying to minimise the death rate of children and pregnant mothers in the community, the organisation successfully brought a change to the community in the health sector though there are a few challenges they encountered that hinder them to fully maximize their capacity to minimise child mortality.